Influence of bone density, screw size and surgical procedure on orthodontic mini-implant placement – part A: temperature development. Issue 4 (April 2021) - Möhlhenrich, S.C.; Heussen, N.; Modabber, A.; Kniha, K.; Hölzle, F.; Wilmes, B.; Danesh, G.; Szalma, J.
Abstract: The aim of this in vitro study was to determine the influence of bone density, orthodontic mini-implant (OMI) size, and the surgical procedure on temperature increase during implant site osteotomy and placement. OMIs of different sizes (2.0 × 7, 2.3 × 7, 2.0 × 11, and 2.3 × 11 mm) were placed in artificial bone blocks of different densities (D1–D4). Optionally, the drilling and insertion angle was 90° or 60° to the bone surface. A total of 640 OMIs were inserted, and predrilling was performed in 320 cases. All insertions were done without irrigation with an axial load of 20N, which resulted in 64 groups. Temperature measurements were performed during implant site preparation and placement using Type-K-thermocouples. Mean temperature increase differed for OMI osteotomy between 1.38 °C and 8.75 °C and placement between 3.8 °C and 18.74 °C, respectively. Critical thermal increase was especially reached during placement using long implants. Increasing bone density and implant size (diameter <length) correlated with thermal increase. Predrilling and angulated implant placement resulted in less heat development. Critical temperature behaviour in high-density bone could be partially responsible for the high failure rates of OMI placement in the lower jaw. The influence of the implant size on temperature development should be considered when selecting an OMI.